2022
DOI: 10.1002/pc.26579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silver nanoparticles on mechanical, thermal and antibacterial properties of poly (vinyl alcohol)/rice hull powder hybrid biocomposite films

Abstract: Earth produces 2.12 billion tons of total wastes annually and nearly 2 million tons of petroleum-based synthetic polymers each day. The majority of synthetic polymers were obtained by packaging applications. Biodegradable films(biofilms) can be a good alternative for pollution-creating synthetic polymers.Rice hull powder (RHP) as reinforcing fillers, polyvinyl alcohol (PVA) as matrix along with silver nanoparticles (AgNPs) were used to prepare the biofilms. By using the solution casting method, five samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, with the filling of 5 wt.% alkali-treated PRSSF as a particulate filler in PVA film, the tensile stress and Young's modulus improved by 9.23% and 4.13%, respectively. The outcomes were similar to those of the earlier report on rice husk hulls, 16 and at-LASP 14 reinforced PVA films.…”
Section: Mechanical Properties Of Pva/at-prssf Biofilmssupporting
confidence: 89%
“…However, with the filling of 5 wt.% alkali-treated PRSSF as a particulate filler in PVA film, the tensile stress and Young's modulus improved by 9.23% and 4.13%, respectively. The outcomes were similar to those of the earlier report on rice husk hulls, 16 and at-LASP 14 reinforced PVA films.…”
Section: Mechanical Properties Of Pva/at-prssf Biofilmssupporting
confidence: 89%
“…[ 16 ] Due to their reciprocal ability to create intermolecular hydrogen bonds between hydroxyl groups, cast films produced from PVA demonstrated good miscibility. Some researchers used agro/municipal waste materials like coconut shell powder, [ 17 ] banana peel powder, [ 18 ] rice hull powder, [ 19 ] and so forth, with PVA and fabricated the biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Limonia acidissima (Wood apple) belongs to the Rutaceae family, which is widely known as the “Stone apple” or “Elephant apple,” the tree is having highly reputed medicinal value. [ 19 ] Limonia Acidissima L. is globally reported from India, Sri Lanka, Pakistan, Java, and Malaysia. In India, it is found to occur in dry regions.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] This versatility provides various characteristics, such as smart/ intelligent or active features, to biopolymer-based materials, offering sustainable alternatives to regular plastics. [15][16][17] Seaweed's versatile applications as a biopolymer have garnered attention in various scientific studies particularly in food, packaging, and pharmaceutical applications. 12 For instance, research conducted by Samsul Rizal and colleagues demonstrated substantial improvements in seaweed film properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous studies have been conducted aiming to enhance biopolymer films with various additives such as clay, cellulose, zinc oxide, silver nanoparticles, montmorillonite, titanium oxide, kaolinite, boehmite and an array of other materials known for their biodegradability and non‐toxic properties 9–14 . This versatility provides various characteristics, such as smart/intelligent or active features, to biopolymer‐based materials, offering sustainable alternatives to regular plastics 15–17 …”
Section: Introductionmentioning
confidence: 99%